Developing Biofilms with Pathogenic Bacteria - Mohsen, Rana Talib (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Microbial communities that develop on living and nonliving surfaces, such as dental tissues or artificial implants, often form complex, structured assemblies known as biofilms. These biofilms enhance microbial survival by providing protection against environmental stressors, including antimicrobial agents. The formation of biofilms contributes significantly to the antibiotic resistance observed in many bacterial populations. Bacillus cereus, a known foodborne pathogen, is capable of forming biofilms and producing toxins that cause gastrointestinal illnesses, including vomiting and diarrhea. Preventing the initial development of biofilms may be more effective than attempting to eliminate mature biofilms, which are notoriously difficult to eradicate. A range of strategies, such as chemical disinfectants, antibiotic therapies, and the application of nanoparticles has been explored to inhibit or disrupt biofilm formation. The significance of microbial biofilms spans various sectors, notably the food and pharmaceutical industries, where contamination and persistent infections pose major concerns. Growing recognition of the link between biofilms and chronic disease has intensified research interest, as bacteria residing in biofilms are often shielded from immune responses and conventional treatments. Current insights into biofilm-associated pathogenesis highlight multiple mechanisms through which biofilms contribute to disease development and persistence.